2008
DOI: 10.1037/0882-7974.23.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Age-related deficits in associative memory: The influence of impaired strategic retrieval.

Abstract: In 2 experiments, the authors investigated whether impaired strategic retrieval processes contribute to the age-related deficit in associative memory. To do so, they compared older and younger adults on measures of associative memory that place high demands on retrieval processes (associative identification and recall-to-reject) to measures that place low demands on such processes (associative reinstatement and recall-to-accept). Results showed that older adults were severely impaired on associative identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
149
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(175 citation statements)
references
References 49 publications
23
149
1
2
Order By: Relevance
“…In line with these considerations, recent studies have found that older adults' propensity for false recognition is not restricted to the DRM paradigm, but also present in tasks that manipulate the familiarity of studied material (Jacoby, 1999;Jacoby, Bishara, Hessels, & Toth, 2005;Jennings & Jacoby, 1997;Pierce, Sullivan, Schacter, & Budson, 2005) or in associative recognition paradigms (Castel & Craik, 2003;Cohn, Emrich, & Moscovitch, 2008). For example, Old and Naveh-Benjamin (2008) tested memory for people and their performance of everyday actions in younger and older adults.…”
mentioning
confidence: 80%
“…In line with these considerations, recent studies have found that older adults' propensity for false recognition is not restricted to the DRM paradigm, but also present in tasks that manipulate the familiarity of studied material (Jacoby, 1999;Jacoby, Bishara, Hessels, & Toth, 2005;Jennings & Jacoby, 1997;Pierce, Sullivan, Schacter, & Budson, 2005) or in associative recognition paradigms (Castel & Craik, 2003;Cohn, Emrich, & Moscovitch, 2008). For example, Old and Naveh-Benjamin (2008) tested memory for people and their performance of everyday actions in younger and older adults.…”
mentioning
confidence: 80%
“…The test list in most associative recognition studies is likely to be a mix of near and far re-pairings, and it is possible, though of course unknown, that older adults' typically higher rate of false alarms (e.g., Castel & Craik, 2003;Cohn et al, 2008;Healy et al, 2005) is partly due to the presence of near-repaired items in the test list. Indeed, this study used only very near and very far re-pairings, and it is unclear what the performance relationship would be to a range of distances.…”
Section: Discussionmentioning
confidence: 99%
“…So for example, older adults are more likely than younger adults to bind together target and distracting information that co-occurs in time (Campbell, Hasher, & Thomas, 2010), as well as irrelevant sequences of distractors that co-occur sequentially (Campbell, Zimerman, Healey, Lee, & Hasher, 2012). Here, we explore the possibility that this tendency toward excessive, or hyper, binding also plays a role in paired-associate learning and so contributes to older adults' typically higher rate of false alarms in associative recognition paradigms (e.g., Castel & Craik, 2003;Cohn, Emrich, & Moscovitch, 2008;Healy, Light, & Chung, 2005).…”
mentioning
confidence: 99%
“…Alternatively, or additionally, integrative and semantic relations could alleviate the age-related memory deficit by inducing retrieval strategies. Indeed, there is evidence to suggest that associative deficits in older adults are a result of retrieval deficits more so than encoding deficits (Cohn, Emrich, & Moscovitch, 2008). In Naveh-Benjamin et al"s (2005) Experiment 2, young and older adults completed an associative memory task with and without a secondary task to divide attention during recall.…”
Section: Discussionmentioning
confidence: 99%